An Ingenious Portrayal of Mythical Traits in Bala Graha (AYUSHDHARA, 2023)
Bala grahas, are a group of organisms, very magnificent divine non human forms that have capability to invade human beings and cause diseases attaining different forms and shapes. Invisible organisms that seize children to cause various illnesses especially those with unrecognized causes can be categorized under the scope of Bala graha. Aim: A novel portrayal of the manifestations of Bala graha to bring in a better opportunity to realize their trait in a more impressing and fascinating manner. Materials and Methods: Bala graha having colossal dimensions cannot be encapsulated easily which paved to the necessity of ingenious portrayal of the same. The approach consisted of thorough searching of several resources which includes Ayurvedic treatises, books, dissertations, conference proceedings and web based scientific databases. The key words that were used for the search consists of Graha, Graha rogas, Bala graha, scientific approach to Bala graha, Bala graha and infectious disorders, pictures of Graha, images of Bala graha. Doing proper literary review revealed that there is sparse tries to enfold Graha rogas and the need to depict the same was considered Conclusion: Bala graha being the untouched and less explored sector of Kaumarabhritya, can be considered eccentric in its origin, invasion, manifestation and management and has very much similarity with infectious disorders. As Grahas attain different size and forms, the depth of the features they produce also varies in its mightiness. Having scrutinized the literature sufficiently arise the need for a new pictorial representation to encapsulate the enormous information regarding the subject matter. This can make the topic much easier to lay hold on and help to recollect the same proficiently.